Surgeons are apprehensive to use DCD lungs despite similar post-transplant outcomes: A 20-year UNOS retrospective analysis - J. Sam Meyer, MSc; Oliver K. Jawitz, MD, MHS; Yury Peysakhovich, MD; Dan Aravot, MD; Matthew G. Hartwig, MD, MHS; Yaron D. Barac, MD, PhD (JHLT Open)
Purpose: As rates of lung transplants in the US grow, waitlist mortality increases. While the literature reports similar survival outcomes of DBD and DCD transplants, research should investigate improvements to DCD lung recovery protocols to increase the total number recovered. Recently, Choi et al. presented donor variables indicative of ultimate lung recovery1. However, expansion of DCD lung transplants requires a comparison of these indicators to DBD donors for application of similar parameters to increase the rate of DCD lung recovery to ensure that viable DCD organs are not discarded due to overly stringent donor and organ requirements. Methods: We performed a retrospective analysis of United Network for Organs Sharing (UNOS) Organ Procurement and Transplantation Network/UNOS STAR (Standard Analysis and Research) database. Donors who donated ≥1 organ from 10/1999–01/2019 were extracted and stratified according to DBD and DCD status. Associated characteristics of potential DCD and DBD lung donors were compared, and a multivariable logistic regression model with ≥1 transplanted lung was constructed to evaluate the independent effects of important predictors. Results: Our data included 179,228 potential lung donors, 162,157 DBD (31,486 donated, 19.4% recovery) and 17,071 DCD (526 donated, 3.1% recovery). Odds of lung non-use between DBD and DCD donors were significantly associated with blood type, alcohol use, cause of death, smoking history, drug use, death circumstance, ethnicity, gender, hypertension, cancer, age, and lung pO2 on 100% P/F ratio (P < 0.001 for all variables). A multivariable regression analysis showed that the odds of a potential DCD donating lungs is 75% lower than (P < 0.001) that of a potential DBD when the cause of death (COD) is stroke, head trauma (44% lower P = 0.076), CNS tumor (22% lower P = 0.174) or MVA (69% lower P = 0.183). A history of diabetes for over 10 years was strongly associated with non-use for DCD lungs (OR, 0.87, P = 0.71), whereas an under 10-year history was associated with increased use (OR 2.33, P = 0.008, OR 1.07 P = 0.819).Lungs from donors ages 40–49 are more likely to be procured than those <30 or >50 in both DBD and DCD. However, likelihood of procurement is 1.84 [95% 1.42, 2.38, p < 0.001] times higher in 40–49-year-old vs. <30-year-old donors when comparing DBD vs. DCD, and 2.43 [95% 1.83, 3.22, p < 0.001] times higher than patients >50 in DBD vs DCD donors. In addition, for each era, the odds for procuring DCD vs. DBD lungs consistently improved [95% 1.46–2.57, p < 0.001].Rejected DCD lungs were associated with donors with higher cardiopulmonary function. Left ventricular ejection fractions in discarded DCD lung donors were higher than those of discarded DBD lung donors (DCD 56.9% ± 13.6 vs. DBD 51.3% ±17.3 P = <0.001). Similar non-use patterns were identified for lung PO2 on 100% O2 (DCD 189.4 ± 121.3 vs. DBD 150.0 ± 106.2 P = <0.001), and when the P/F ratio was above 350.00 (DCD 13.5% vs. DBD 7.7% P = <0.001). Conclusion: Despite literature reporting comparable survival of DCD and DBD organs, this study highlights discrepancies in lung procurement practices that evaluate donor characteristics differently in DBD and DCD donors. Further study should investigate whether similar discrepancies exist in the procurement process of other organs.